A novel virotherapy encoding human interleukin-7 improves ex vivo T lymphocyte functions in immunosuppressed patients with septic shock and critically ill COVID-19 - Crausaz, Morgane; Monneret, Guillaume; Conti, Filippo; Lukaszewicz, Anne-Claire; Marchand, Jean-Baptiste; Martin, Perrine; Inchauspé, Geneviève; Venet, Fabienne (Frontiers in Immunology, 2022)
A majority of patients with sepsis surviving the first days in intensive care units (ICU) enter a state of immunosuppression contributing to their worsening. A novel virotherapy based on the non-propagative Modified Virus Ankara (MVA) expressing the human interleukin-7 (hIL-7) cytokine fused to an Fc fragment, MVA-hIL-7-Fc, was developed and shown to enhance innate and adaptive immunity and confer survival advantages in murine sepsis models. Here, we assessed the capacity of hIL-7-Fc produced by the MVA-hIL-7-Fc to improve ex vivo T lymphocyte functions from ICU patients with sepsis. Primary hepatocytes were transduced with the MVA-hIL-7-Fc or an empty MVA, and cell supernatants containing the secreted hIL-7-Fc were harvested for in vitro and ex vivo studies. Whole blood from ICU patients [septic shock = 15, coronavirus disease 2019 (COVID-19) = 30] and healthy donors (n = 36) was collected. STAT5 phosphorylation, cytokine production, and cell proliferation were assessed upon T cell receptor (TCR) stimulation in presence of MVA-hIL-7-Fc–infected cell supernatants. Cells infected by MVA-hIL-7-Fc produced a dimeric, glycosylated, and biologically active hIL-7-Fc. Cell supernatants containing the expressed hIL-7-Fc triggered the IL-7 pathway in T lymphocytes as evidenced by the increased STAT5 phosphorylation in CD3+ cells from patients and healthy donors. The secreted hIL-7-Fc improved Interferon-γ (IFN-γ) and/or Tumor necrosis factor-α (TNF-α) productions and CD4+ and CD8+ T lymphocyte proliferation after TCR stimulation in patients with bacterial and viral sepsis. This study demonstrates the capacity of the novel MVA-hIL-7-Fc–based virotherapy to restore ex vivo T cells immune functions in ICU patients with sepsis and COVID-19, further supporting its clinical development.